Perancangan Sistem Perpustakaan Digital Berbasis Web Pada MTs Daarul Muqimien Menggunakan Extreme Programming (Prototype) - Ai Nuril Aini; Kussigit Santosa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Developments in various fields require the library to make changes, both in management and service. Libraries are usually used by visitors as a medium for seeking knowledge, information and references. As technology develops, there are currently many libraries available in different forms, namely electronic libraries or various other names such as digital libraries, wallless libraries, virtual libraries and many others. The administration system that runs in the Mts Daarul Muqimien library is still manual so a web-based digital library is needed to facilitate library management. The research method for developing this system is the researcher using the Extreme programming method. Extreme programming is an engineered software development methodology and is one of agile software development. Extreme programming consists of several parts, namely planning, design, coding, and testing systems. The testing method used in this digital library system is the black box method. This method tests the system functionally.